Field evaluation of peanut genotypes for resistance to Sclerotinia blight - Akem, C.N.; Melouk, H.A.; Smith, O.D. (Elsevier, 1992)
Nineteen peanut genotypes were evaluated for resistance to Sclerotinia blight caused by Sclerotinia minor in small field plots at Stillwater, Oklahoma, USA, in 1986, 1987 and 1988. Entries were arranged in a completely randomized block design in field plots with four replications. Average disease incidence (%) at harvest for the most resistant genotypes TX 804475, Toalson, TX 798731, TX 798683, and TX 798736 was 1.6, 3.9, 6.7, 9.1 and 11.6, respectively; the most susceptible genotypes, Florunner, Okrun and OK FH-15 had average disease incidence values of 93.4, 93.5 and 91, respectively. Incidence of S. minor was recorded throughout the growing season, and data were logistically transformed to determine disease progress. Average disease progress values (r) were 0.006, 0.002, 0.003, 0.004 and 0.006, for the resistant genotypes Toalson, TX 804475, TX 798731, TX 798683 and TX 798736, respectively; Florunner and its three hybrids (OK-FH 13, 15, and Okrun) had r values of 0.13, 0.12, 0.12 and 0.14, respectively. Other genotypes had varying degrees of resistance. Generally, genotypes with a bunch growth habit exhibited a lower incidence of Sclerotinia blight than those with a prostrate growth habit. These results were generally in agreement with greenhouse tests using a detached shoot technique to evaluate the genotype reaction to S. minor.